Monitoring stress and wellness in elite athletes undertaking tertiary study - Wilkes, D. S. (Lincoln University, 2018)
Athletes undertaking full-time sporting commitments alongside full-time tertiary studies (commonly known as sport scholars) are a unique population because of the need to perform to a high level in both sport and academic studies. For a sport scholar, academic workload creates significant stress which can add to the constant pressure to perform athletically. Sport scholars are forced to cope with issues such as missing class, extended travel, and added demands that non-athletes do not experience. Additional stressors include; time availability and management, social and organisational skills, and physiological and psychological developmental challenges. Students undertaking tertiary study are a vulnerable population to sleep difficulties, depression, anxiety, feelings of hopelessness, exhaustion, and a sense of being overwhelmed. The aim of this study was to investigate subjective measures along with training measures to better understand the pressures sport scholars undergo, as well identifying times throughout the academic year where overall stress levels were counterproductive for an athlete`s overall wellbeing. This study focused on 183 (132 male and 51 female) undergraduate sport scholars aged 18-25 years old at Lincoln University, Christchurch, New Zealand over a 4-year period, who were part of a scholarship programme. These participants were combining full-time tertiary study with full-time sport and training commitments. Athletes were required to enter their daily subjective well-being and training throughout the academic year as part of their scholarship programme. For this study, psychological measures of wellness such as academic pressure, energy levels, mood state, muscle readiness, sleep duration, and sleep quality, as well as training measures such as weekly training load and weekly training volume were used from the sport scholars` daily entries. The average completion rate for subjects entering their weekly subjective data was 34% in semester 1 and 21% in semester 2. Similarly, in semester 1 only 20% of subjects entered their weekly training data which reduced to 10% by semester 2. All year levels demonstrated lower levels of wellness through subjective measures one week before exams, as well as during exams, before improving directly after exams and during breaks. Third-year sport scholars demonstrated the highest academic pressure, weekly training volume, and weekly training load, as well as the lowest energy levels, mood state, sleep duration, and sleep quality during the academic year. Mood state and sleep duration were substantially decreased for third-year sport scholars, with mood state being as low as 3.1 ± 1.21 (mean ± SD) on a 1-5 Likert-type scale during week 35 of the academic year, and sleep duration as low as 6.8 hours ± 1.37 during week 40 of the academic year. Female athletes demonstrated decreased levels of wellness compared to male athletes, including lower mood state (3.4 ± 0.8 / 3.7 ± 0.7), energy levels (3.3 ± 0.8 / 3.7 ± 0.6), and sleep quality (3.2 ± 0.8 / 3.6 ± 0.8). Data are mean ± SD for female and males respectively. We found that mood state had the highest association with academic pressure (r = 0.30), indicating a moderate association between how an athlete`s mood state is and how they perceive their academic stress. Using a step-wise regression analysis to investigate what combination of subjective measures might have an influence on athlete`s academic pressure, we found the combination of energy levels, mood state, muscle readiness, sleep quality and readiness to train was strongly associated with academic pressure (r = 0.66). This study found that there are certain times throughout the academic year where sport scholars are more vulnerable to stress, (e.g., during exams), as well as certain groups that require greater support (e.g., third-year athletes and female athletes). Maintaining an athlete`s energy levels, mood state, muscle readiness, and sleep quality can help reduce their levels of academic pressure. These findings suggest the need for immediate interventions to be put in place to better support athletes stress leading up to exams, as well as the need to better support third-year athletes and female athletes to help them manage stress better, and to improve their wellness. In conclusion, we found that athletes undertaking full-time tertiary study alongside their full-time training commitments were vulnerable to increased levels of psychological stress. Implications of these findings are further considered